Public procurement spend analysis at a national level in Finland. Issue 2 (3rd June 2019) - Kivisto, Timo; Virolainen, Veli Matti
Abstract : Purpose: The purpose of this paper is to make a contribution for the unclear boundaries of public procurement in accounting terms. International organizations, public organizations' national control entities and managers are interested in monetary spend. Public procurement literature and the system of national accounts lack proper definitions of public procurement in accounting terms or are framed by legal procedures. Design/methodology/approach: The authors draft clear monetary definitions for procurement boundaries and develop an alternative, more refined bottom-up method of calculating public procurement spend. Findings: The calculation for Finland is based on reliable secondary data and shows considerably higher procurement spend than traditional SNA statistics or procurement notices. Originality/value: The calculation can be replicated in other countries using the 2008 SNA coding for organizations. The paper highlights the need to address in-house procurement in future research.